How curiosity affects contextual performance: An emotional daily dynamics perspective - Junça Silva, A.; Caetano, A. (International Journal of Manpower, 2024)
Purpose This research relied on the broaden-and-build (B&B) theory to explore emotional predictors for curiosity-related differences in daily engagement and contextual performance. We tested a moderated mediation model, arguing that daily positive emotions would be related to daily work engagement and contextual performance. Design/methodology/approach A total of 586 participants participated in a five-day diary study (n = 2379). Findings Multi-level modeling showed that, at the person level of analysis, daily positive emotions were significantly and positively related to daily work engagement and, in turn, daily performance. At the daily level of analysis, the mediation model was moderated by curiosity, such that it became stronger for individuals who scored higher on curiosity. Originality/value These findings make relevant theoretical contributions to understanding the power of curiosity for daily emotional dynamics in organizations. Compared to traditional between-person variables, these results also expand knowledge on within-person processes that explain daily work engagement and contextual performance. In sum, this study shows that “curiosity does not kill the cat”; instead, it makes it productive.